Penerapan model pembelajaran means ends analysis untuk meningkatkan keterampilan penalaran bangun datar pada peserta didik kelas iv sekolah dasar - Hidayat, Arif Wahyu; Poerwanti, Jenny Indrastoeti Siti; Surya, Anesa; Sutoyo, Sutoyo (Universitas Sebelas Maret, 2019)
Abstract. The purpose of this research is to improve the reasoning skills in the plan figure by applying Means Ends Analysis learning model. The subjects of this research were students of IV class at SDN Serengan II Surakarta in the 2018/2019 academic year, totalling 28 students. This research is a Classroom Action Research with three cycles. Data collection techniques are using observations, interviews, test and documentation. Data validity tests are using technique triangulation. Interactive model of Miles-Huberman was used to data analysis technique. The initial condition of reasoning skills of IV class the average value class score of 32,64 with 0% in classical completeness. The first cycle began with the first learning resulting in increased 7,14% with 41,00 of average, second learning was 21,43% with 49,14 average. The study continued with second cycle with percentage 57,14% with average 68,79, second learning was 50% with 72,68 average. The study continued with third cycle with the percentage was 78,57% with 77,07 average, second learning was 85,71% with 81,21 average. Based on the results, it can be concluded that through the application of the Means Ends Analysis model can improve the reasoning skills in class IV SDN Serengan II Surakarta 2018/2019 academic year.